Luaran Klinis Pneumonia Akibat Pseudomonas Aeruginosa Extensively Drug-Resistant Pada Pasien Lansia Pasca-Stroke: Laporan Kasus Berbasis Bukti - Lasrina Simarmata; Sarah Christina Samosir; Robinson Josua Lase; Dhany Rynando Zega; Bryan Pratama Saragih (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Pneumonia caused by extensively drug-resistant (XDR) Pseudomonas aeruginosa is still  clinicaly chalenging, particularly among geriatric patients with neurological comorbidities such as stroke. This report presents a case of XDR P. aeruginosa pneumonia complicated by sepsis in a 73-year-old patient, characterized by persistent leukocytosis until the tenth day of hospitalization despite empirical meropenem therapy. This evidence-based case report aims to analyze clinical outcomes, specifically 28-day and 30-day mortality rates, and to identify mortality predictors in the adult population through a systematic literature search of the PubMed and Google Scholar databases for the 2019–2026 period. Synthesized evidence from six core studies indicates that XDR P. aeruginosa infections carry a profoundly high 28-day mortality rate, ranging from 41% to 51% in cohorts receiving antibiotic monotherapy. Key mortality predictors identified include the presence of sepsis or septic shock, a delay in initiating adequate therapy exceeding 52 hours, advanced age, and the requirement for Intensive Care Unit (ICU) admission. The phenomenon of persistent or worsening leukocytosis during treatment, as observed in this case, serves as a critical clinical indicator associated with antimicrobial response failure and a dismal prognosis. Ultimately, XDR P. aeruginosa pneumonia is associated with poor clinical outcomes, where therapeutic success is strictly contingent upon the timely administration of antibiotic regimens with proven activity against these highly resistant isolates.